Psychology and Culture: The Construct of Psychological Capital of Collective Culture H.E.R.O (Hope, Efficacy, Resilience, Optimism) in The Kebo- Keboan Tradition of Using Tribe, Banyuwangi: Psikologi dan Budaya: Konstruk Modal Psikologis Kultur Kolektif H.E.R.O (Hope, Efficacy, Resilience, Optimism) dalam Tradisi Kebo- Keboan Suku Using, Banyuwangi - Ivy Novenatha Karolina Tambun; Marselius Sampe Tondok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The Using Tribe in Banyuwangi has many distinctive cultures that can attract tourists from foreign countries, because their rituals are known to have magical nuances. One of the traditions is the Kebo-Keboan/Keboan ceremony which is especially preserved by the residents of Alasmalang and Aliyan Village. This study aims to explore the social psychological values ​​contained in the Kebo-Keboan/Keboan tradition of the Using Tribe. Based on this conceptual exploratory study, the results show that the origins, the series of ceremonial processions and efforts to preserve this tradition contain aspects of psychological capital in the context of collective society, known as H.E.R.O (Hope, group- Efficacy, Resilience, Optimism). The findings of this psychology and cultural study can contribute to ideas to enrich insights in the field of cultural psychology in the context of an agrarian-collective society, and can also increase appreciation of cultural diversity to strengthen social cohesiveness in a pluralistic Indonesian society.